THEMATIC CARTOGRAPHY IN GEO-ENVIRONMENTAL RESEARCH - Sann, Janine Gisele (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
This work presents Cartography as a language that represents facts and geographical phenomena. Thematic Cartography has specifications that interfere in the process of visual translation of geographical information. It emphasizes that the cartographer needs to know the graphic language and the limits of bi-dimensional representation in order to choose the visual variants compatible with the implicit meaning of the information to be translated. It analyzes and effectuates graphic corrections of several classic documents in scientific literature according to Semiology of Graphics. It presents and describes the method to structure the legend of a synthetic poly-thematic map applied to the case study of a diagnostic geo-environmental map of the Hydroelectric Power Igarapava Plant.